VULNERABILITY TEST OF Aedes aegypti LARVA AGAINST TEMEFOS IN WAY KANDIS, BANDAR LAMPUNG - Nurul Hanifah; EMANTIS ROSA; Endah Seytaningrum (Jurnal Ilmiah Biologi Eksperimen dan Keanekaragaman Hayati (J-BEKH), 2020)
Aedes aegypti is a major vector of Dengue Fever (DHF) that is spread through mosquito bites. However, Bandar Lampung ranked 3rd out of 15 districts in Lampung Province with an IR (Incidence Rate) of 59.43. One way to reduce dengue cases is vector control. Temefos is commonly used as a chemical vector's control and it is possible can cause resistance to larvae. The information about Aedes Aegypty has not been widely known about larval of Aedes aegypty's susceptibility towards Temefos in Lampung Province. Therefore, this study aims to determine the susceptibility status of Aedes aegypti larvae towards Temefos in Way Kandis Village, Tanjung Senang Regency, Bandar Lampung. This research was conducted in December 2018 - February 2019. This study uses five different temefos concentrations, i.e ;0 mg / L concentration as control, 0.005 mg / L, 0.01 mg / L, 0.02 mg / L, and 0 , Each 03 mg / L was repeated in 4 times. Observations were made by calculating the number of larvae that fainted, died, and lived. The results show that the susceptibility of Aedes aegypti towards Temefos in Way Kandis Village, Tanjung Senang Regency, Bandar Lampung City, is categorized as susceptible in the concentration range of 0.005 - 0.03 mg / L.